Reversible activation of pH-sensitive cell penetrating peptides attached to gold surfaces. Issue 2 (20th October 2014) - Baio, Joe E.; Schach, Denise; Fuchs, Adrian V.; Schmüser, Lars; Billecke, Nils; Bubeck, Christoph; Landfester, Katharina; Bonn, Mischa; Bruns, Michael; Weiss, Clemens K.; Weidner, Tobias
Abstract : Here, we demonstrate that a fusion protein mimic, designed to achieve a reversible, pH-driven helix-coil transition mechanism, retain its functionality when covalently bound to a surface. Abstract : pH-sensitive viral fusion protein mimics are widely touted as a promising route towards site-specific delivery of therapeutic compounds across lipid membranes. Here, we demonstrate that a fusion protein mimic, designed to achieve a reversible, pH-driven helix-coil transition mechanism, retains its functionality when covalently bound to a surface.